Habituation of Long-Tailed Macaque Toward Labyrinth-shaped Capture Cage in the Captive Breeding Station on Tinjil Island, Pandeglang, West Java - Entang Uskandar; Yanto Santosa (Department of Forest Resources Conservation and Ecotourism - IPB University, 1992)
One of the Important th ngsto make it easier to capture monkey IS to know the monkey's habituation and the length of stay In the feeder cage. Some of the monkey's group in Tinjil Island had habituated loward the extra food schedule. Ihey generally come to feeder cage when extra food is gtven. The orderof entrance to feeder cage to take and eat the extra Iood I ;I( first the dominant male followed by the lower rank adult males, then adult females, young males. young lcmalcs and children. ?'his order ofentrance is based on rank and animal bravery. Monkey's length of stay in the feeder cage has about the same ordcr as the entrance order to the feeder cage. adult males. adult females, young males, young females and rh ldrcn.